The factory as a representation of video game dystopias - Francesco Toniolo (Griseldaonline, 2021)
This paper explores the representations of factories in video games, in relation to dystopian fictional worlds. The representation of the factory, its role in video game storytelling, its connection with game design elements, are connected to the ways in which this building is a concrete embodiment of a dystopic system of power. The research is introduced by a brief survey of factories in video games. Then, this paper presents three progressive models, linked to three concrete examples: Beyond Good & Evil (Ubisoft, 2003), Amnesia: A Machine For Pigs (The Chinese Room, 2013) and NieR: Automata (Platinum Games, 2017). Finally, the contribution ends with a fourth category, linked to explicitly political video games.